2016
DOI: 10.1590/1806-9061-2015-0127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antimicrobials on Salmonella Spp. Strains Isolated from Poultry Processing Plants

Abstract: The routine use of antimicrobials in animal production for the treatment of infections, disease prevention, or as growth promoters is a predisposing factor for the development and dissemination of antimicrobial resistance. In food industries, sanitizers are used for the control of microbial colonization, and their efficacy depends on contact time and on the dilution of the products used. The present study assessed the effect of 12 antimicrobials and four commercial sanitizers on 18 Salmonella spp. strains isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…High resistance to third generation Cephalosporins as well as to the Penicilins, Tetracyclines and Chloramphenicol has been reported in Nigeria [44]. S. Typhimurium exhibiting antibiotic resistance has also been reported in many parts of the world [45,46,47,48]. The observed high levels of resistance is therefore an indication that these antibiotics are nonsusceptible to the isolates particularly those from poultry origin within the study area.…”
Section: Antibiotic Resistance In Thementioning
confidence: 86%
“…High resistance to third generation Cephalosporins as well as to the Penicilins, Tetracyclines and Chloramphenicol has been reported in Nigeria [44]. S. Typhimurium exhibiting antibiotic resistance has also been reported in many parts of the world [45,46,47,48]. The observed high levels of resistance is therefore an indication that these antibiotics are nonsusceptible to the isolates particularly those from poultry origin within the study area.…”
Section: Antibiotic Resistance In Thementioning
confidence: 86%
“…The isolated strains of the present study showed resistance to streptomycin (10%) in poultry samples, while Adesiji et al (2011) revealed that the examined Salmonella isolates from pork meat samples were sensitive to ciprofloxacin and tetracycline by 100% but all were resistant to amoxicillin. Mion et al (2016) reported the sensitivity of Salmonella isolates isolated from poultry processing plants against ciprofloxacin by 94% and ampicillin by 77%, respectively. The current study showed resistance against ampicillin and erythromycin in 66.6% and 63.6%, respectively, in contrast to 100% resistivity of ampicillin and erythromycin in Dorgham et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only one strain (5%) was non-susceptible among those isolated in 2006. The resistance of Salmonella to tetracycline is variable in the literature (Mion et al 2016, El-Tayeb et al 2017, Nair et al 2018, Borges et al 2019. A recent study found high non-susceptibility rates among S. Heidelberg isolated from Brazilian flocks (Neves et al 2020).…”
Section: Discussionmentioning
confidence: 99%